PLANNING OF CLEAN WATER DISTRIBUTION PIPELINE NETWORK AT UNIVERSITAS JAMBI KAMPUS PINANG MASAK MENDALO - Freddy Ilfan; Winny Laura; Eki Kurniadi (LPPM Universitas Negeri Jakarta, 2023)
In 2021 it is estimated that there are 19,836 people at Universitas Jambi Kampus Pinang Masak Mendalo. One of the most important aspects to support activities in Universitas Jambi Kampus Pinang Masak Mendalo is a clean water supply. This study aims to determine clean water needs, to analyse hydraulic factors such as water discharge, flow speed, water pressure, and head loss using EPANET program, and to calculate the budget required to build a water distribution pipeline system. The results of water distribution pipeline network design are clean water needs at Universitas Jambi Kampus Pinang Masak Mendalo as much as 665,910 liters/day or 18.4975 liters/second and at the maximum daily needs as much as 732,500 liters/day or 20.3472 liters/second in the projected year of 2031. Analyses of hydraulic factors in the pipeline distribution system using EPANET program and manual calculation give the same results, but there are some pipe segments that do not fulfill of flow velocity standard, that are on pipe A1 = 0.15 m/s, B1 = 0.08 m/s dan pipa B2 = 0.25 m/s. The cost required to build a clean water distribution pipeline network at the Universitas Jambi Kampus Pinang Masak Mendalo, is amounting Rp238,252,263.00,-